Revitalizing Customary Law as a Source of Law in Building the Indonesian Legal System - Wahida Ariyanti Nasution; Luthfi Daulay (Program Pascasarjana UIN Sumatera Utara Medan, 2021)
The neglect of customary law as a source of law in Indonesia is partly due to the assumption that customary law is very traditional and cannot accommodate modern developments (globalization and technology). This study examines which areas of customary law are still relevant in addressing the problems faced by the Indonesian nation in the era of globalization, and how urgent customary law is as a basis for national legal development policies. This study uses a descriptive analytical research method with a normative juridical approach, where data and information will be collected both in terms of its assessment and management are carried out interdisciplinary and multidisciplinary and cross-sectoral. The data and information are then analyzed in depth through normative juridical to obtain a picture of customary law. The results of the study indicate that some customary legal institutions, including inheritance law, customary rights, mortgages, rent, and profit sharing, are still relevant and can be a source of inspiration for the formation of national law and become a source of law in the process of legal discovery. In addition, the existence of these institutions can be used as a reference in the formation of national law and play an important role as a source in the process of legal discovery in Indonesia.